2020
DOI: 10.3390/e22050535
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Entropy Based Deep Neural Network Model for Road Extraction from Satellite Images

Abstract: This paper proposes a deep convolutional neural network model with encoder-decoder architecture to extract road network from satellite images. We employ ResNet-18 and Atrous Spatial Pyramid Pooling technique to trade off between the extraction precision and running time. A modified cross entropy loss function is proposed to train our deep model. A PointRend algorithm is used to recover a smooth, clear and sharp road boundary. The augmentated DeepGlobe dataset is used to train our deep model and the asynchronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…We concluded that these imperfections were caused by the complex nature of the geospatial object (roads have large curvature changes, different materials used in the pavement, different widths, depending on the importance of the route, and very often have no clearly defined borders) by the presence of occlusions in the scenes, and by the limitation of existing semantic segmentation algorithms. These imperfections and errors are in line with issues raised by other investigations, as similar problems were identified in other works tackling the road extraction task from high-resolution remote sensing images [2], [3], [4], [5], and are very problematic when pursuing a large-scale road extraction operation for automatic mapping purposes. As a consequence, we consider that adding a post-processing operation to improve the initial segmentation predictions is essential for a successful road extraction.…”
Section: Introductionsupporting
confidence: 82%
“…We concluded that these imperfections were caused by the complex nature of the geospatial object (roads have large curvature changes, different materials used in the pavement, different widths, depending on the importance of the route, and very often have no clearly defined borders) by the presence of occlusions in the scenes, and by the limitation of existing semantic segmentation algorithms. These imperfections and errors are in line with issues raised by other investigations, as similar problems were identified in other works tackling the road extraction task from high-resolution remote sensing images [2], [3], [4], [5], and are very problematic when pursuing a large-scale road extraction operation for automatic mapping purposes. As a consequence, we consider that adding a post-processing operation to improve the initial segmentation predictions is essential for a successful road extraction.…”
Section: Introductionsupporting
confidence: 82%
“…We also identified higher rates of "false positive labels in areas where the materials used in the road pavement have a similar spectral signature with their surroundings, or areas where geospatial objects with similar features are present (such as dry riverbeds, railroads, or irrigation canals) and higher rates of false negatives in sections where other objects cover large portions of the roads were covered" (page 13 in [8]). Similar problems are still observed in recent works dealing with the road extraction from high-resolution aerial imagery-improving the road extraction task is an active area of research [11][12][13][14].…”
Section: Introductionsupporting
confidence: 61%
“…The contribution by Shan and Fang [ 2 ], “A Cross Entropy Based Deep Neural Network Model for Road Extraction from Satellite Images,” proposes a deep convolutional neural network model with an encoder-decoder architecture to extract a road network from satellite images. The authors employ ResNet-18 and atrous spatial pyramid pooling technique to tradeoff between the extraction precision and running time.…”
Section: Themes Of This Special Issuementioning
confidence: 99%